Fractional Sliding Mode Guidance Law for High Speed Maneuvering Targets - Tang Xiao, Ye Jikun (Editorial Office of Aero Weaponry, 2021)
Aiming at the interception problem of high speed maneuvering targets, a guidance law design scheme based on fractional-order sliding mode control theory is proposed. First, with the idea of fast terminal sliding mode plane, fractional order terms of line-of-sight angle rate are introduced into the fast terminal sliding mode dynamic plane to construct a fractional order dynamic sliding mode hyperplane. Then, combined with fractional calculus theory, the fractional sliding mode guidance law is derived on the basis of fractional dynamic sliding mode hyperplane, and the stability of fractional sliding mode guidance law is proved by using infinite state method and Lyapunov stability theory. The simulation results show that the guidance law can make the line-of-sight angle rate converge within 2 s, the average overload is small, the guidance accuracy is higher, and the terminal miss distance is within 0.5 m.